Determinan Tingkat Pendidikan Tenaga Kerja di Desa Beraban, Kediri, Kabupaten Tabanan - Ni Wayan Diah Okta Wardani; Made Dwi Setyadhi Mustika (Lembaga Pengembangan Kinerja Dosen, 2025)
The challenge regarding the quality of the workforce in Indonesia is still a major problem because the majority of the workforce are only elementary school graduates. The quality of human resources in Bali is still low compared to foreign workers working in Bali. Tanah Lot will be the most visited place by domestic tourists in 2024. Tanah Lot, which is located in Beraban Village, Kediri, Tabanan, makes Beraban Village the village most involved in tourism management including the provision of tourism support facilities. This condition requires Beraban Village to have a qualified and highly competitive workforce. This study aims to analyze the effect of parental income, father's education, mother's education, parental dependents, job opportunities, and scholarships simultaneously and partially, and to determine the variables that have the most dominant influence on the level of education of the workforce in Beraban Village. The sample used was 120 people with a simple random sampling method. The analysis techniques used were descriptive analysis, confirmatory factor analysis (CFA), and multiple linear analysis. The results of this study indicate that parental income, father's education, mother's education, parental dependents, job opportunities, and scholarships simultaneously affect the level of education of the workforce. Father's education, mother's education, and job opportunities partially have a positive and significant effect on the level of education of the workforce. While the variables of parental income, parental dependents, and scholarships partially do not have a significant effect on the level of education of the workforce. Mother's education has the most dominant influence on the level of education of the workforce. Parents who have higher education can provide a better understanding of education and can encourage them to continue their education to a higher level.